2021
DOI: 10.1111/are.15692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different chromium sources on growth performance, serum biochemical, hepatopancreas glycometabolism enzymes activities, IR, GLUT2 and SGLT1 gene expression of common carp ( Cyprinus carpio )

Abstract: A 60‐day feeding trial was conducted to evaluate the effects of different chromium sources on the common carp. Four diets (32.2% crude protein and 6% lipids of dry matter) were formulated to add chromium oxide (Cr2O3), chromium picolinate (CrPic) and chromium methionine (CrMet) with 2 mg/kg Cr3+, respectively, and one basal diet. Each diet was randomly assigned to triplicate groups of 60 juvenile common carp (approximately 40.95 ± 4.80 g). The results indicated that fish fed CrMet diets had significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
3
1
2
Order By: Relevance
“…Results suggest that supplementation with organic CrMet is beneficial for the nutritious value of commercially based diets for African catfish. This positive effect is in accordance with Cui et al [ 18 ], who demonstrated that dietary CrMet supplementation is superior in comparison with inorganic Cr and Cr picolinate in common carp due to increased absorption efficiency. Dietary CrMet supplementation also improved the growth performance of common carp in earlier research [ 8 ] and of different crustacean species [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Results suggest that supplementation with organic CrMet is beneficial for the nutritious value of commercially based diets for African catfish. This positive effect is in accordance with Cui et al [ 18 ], who demonstrated that dietary CrMet supplementation is superior in comparison with inorganic Cr and Cr picolinate in common carp due to increased absorption efficiency. Dietary CrMet supplementation also improved the growth performance of common carp in earlier research [ 8 ] and of different crustacean species [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…According to Pechova and Pavlata [3], the absorption efficiency of inorganic Cr +3 is inversely proportional to the dietary level. A similar trend was also observed in the present study with organic Cr supplementation, somewhat contradicting observations from Cui et al [18]. However, the analyzed content of Cr in diets differed from the expected values from organic supplementation (Tables 3 and 4), which was most likely caused by contamination with inorganic Cr during feed production.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations